Gestantes infectadas pelo HIV : análise das condutas utilizadas na prevenção da transmissão vertical do vírus da imunodeficiência humana (HIV) em Fortaleza, Ceará no período de 1999 a 2001 - Cavalcante, Maria do Socorro (2003)
In the last 20 years the human immunodeficiency virus (HIV) infection epidemic is presenting all over the world in a growing way the women’s population. In that context, the HIV transmission from mother to infant appears as one of the challenges for the public health. Several studies are confirming the effectiveness of zidovudine in reduction of HIV transmission from mother to infant. In Brazil, since 1996, the recommendations of the ACTG 076 protocol have begun. In Ceara, the actions were systematized starting from 2000 without, however, being submitted to evaluation. The purpose of this study was to identify pregnant women infected by HIV and to analyze different ways to prevent HIV transmission from mother to infant in the period from 1999 to 2001 in Fortaleza, Ceara. In a first stage, from the databases relationship of the Public Health Central Laboratory and from the Newborn Information System with subsequent active search in subject medical records. After these two stages, 138 women infected by HIV that had their children in public maternities of Fortaleza were identified. The sub-notification found in this study was 70.3% of the cases. Only 47.5% of the pregnant women that accomplished prenatal had the opportunity to accomplish in a correct way all of the stages of the prophylaxis for the prevention of HIV transmission from mother to infant, including the conducts in the newborn. As for the closure of the 138 born children’s cases, 37.0% had continuation loss. According to the exposed, we come to the conclusion that there are still losses in the accomplishment of all stages of prophylactic conducts and loss in the exposed child’s following up, damaging the knowledge of the reduction in the HIV transmission. The need of optimization of surveillance and intervention actions is emphasized for the implementation of those actions.